GRICE’S MAXIM OF JENNIE’S BLACKPINK INTERVIEWS IN ELLE MAGAZINE AND BILLBOARD MUSIC - Arfiawati, Fristi; Kharina Salzadilla (Jurnal Sastra - Studi Ilmiah Sastra, 2024)
The research entitled Grice’s Maxim of Jennie’s Blackpink Interviews in Elle Magazine and Billboard Music applied the theory proposed by Grice in Levinson (1983) and Cutting (2002). The aim is to investigate the types of Grice’s maxim in Jennie’s Blackpink interviews in Elle magazine and Billboard music. Furthermore, this research used descriptive qualitative method. The data which were classified and analized were taken from YouTube. The result showed that there were 15 data cooperated with maxim quantity, 25 Data cooperated with maxim quality, 22 data cooperated with maxim relevance, and 3 data cooperated maxim of manner. In addition, there are 10 data violate maxim quantity, 1 datum violates maxim quality, and 3 data violate maxim relevance. Thus, the most dominant maxim which was found in Jennie’s Blackpink interview is maxim quality and the most dominant maxim that is violated in the interview is maxim quantity.